1976
DOI: 10.1073/pnas.73.6.1926
|View full text |Cite
|
Sign up to set email alerts
|

Extracytoplasmic adenylate cyclase of Bordetella pertussis.

Abstract: Soluble adenylate cyclase [EC 4.6.1.1] accumulates in the culture medium of exponentially growing Bordetella pertussis (300-900 pmol of cAMP formed/min per ml of 24 hr culture supernatant). In addition, there is an extracytoplasmic adenylate cyclase which enables the intact organisms to form [32P] cAMP (adenosine 3':5'-cyclic monophosphate) from exogenous [alpha-32P] ATP (200-1200 nmol of cAMP formed/min per g wet weight of cells) and which comprises 20-45% of the total adenylate cyclase activity. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
1

Year Published

1977
1977
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 24 publications
3
81
0
1
Order By: Relevance
“…Murine monoclonal antibodies used for detection were BPH2, specific for serotype 2 fimbrial subunit (4a). BPE3, specific for pertactin (5); and 9D4, specific for adenylate cyclase toxin (13). BPH2 and BPE3 were kindly provided by LacZ' and may be Hly-as well.…”
Section: Methodsmentioning
confidence: 99%
“…Murine monoclonal antibodies used for detection were BPH2, specific for serotype 2 fimbrial subunit (4a). BPE3, specific for pertactin (5); and 9D4, specific for adenylate cyclase toxin (13). BPH2 and BPE3 were kindly provided by LacZ' and may be Hly-as well.…”
Section: Methodsmentioning
confidence: 99%
“…Our results demonstrate Bvg-dependent activation of a ptxA-lacZYA fusion in E. coli and indicate that bvg is the only Bordetella locus required for ptxA activation in this heterologous system. Bordetella pertussis, the causative agent of whooping cough, synthesizes toxins and adhesins which appear to aid the bacterium in colonization and multiplication (15,23,28,38,56,59). Expression of toxins (pertussis toxin, adenylate cyclasehemolysin, and dermonecrotic toxin) and adhesins (filamentous hemagglutinin, fimbriae, and pertactin) is positively regulated by the products of the bvg operon (11,57,59).…”
mentioning
confidence: 99%
“…Low concentrations of extracellular cAMP after growth in C media cannot be accounted for by direct inhibition of adenylate cyclase activity by pro-C-mode salts, as most of these caused no more inhibition than did the pro-X-mode salt NaCI. The moderate inhibition caused by NaCl, Na,SO,, sodium succinate and sodium butyrate was presumably due to Na+ ions which Hewlett & Wolff (1976) reported to cause mild inhibition of adenylate cyclase activity. The inhibition caused by nicotinic acid and nicotinamide was more marked (about 60:; loss of activity).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, however, 100 'C for 10 min destroyed all detectable adenylate cyclase activity in B. pertussis intact cells. Hewlett & Wolff (1976) also reported that purified adenylate cyclase from B. putussis lost 90"" of its activity after 20 min at 56 "C. Clearly, further investigation of the effects of B. pertu.ssis adenylate cyclase on neutrophil function is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation